2021
DOI: 10.1016/j.bioactmat.2021.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed detection and differentiation of bacterial enzymes and bacteria by color-encoded sensor hydrogels

Abstract: We report on the fabrication and characterization of color-encoded chitosan hydrogels for the rapid, sensitive and specific detection of bacterial enzymes as well as the selective detection of a set of tested bacteria through characteristic enzyme reactions. These patterned sensor hydrogels are functionalized with three different colorimetric enzyme substrates affording the multiplexed detection and differentiation of α-glucosidase, β-galactosidase and β-glucuronidase. The limits of detection of the hydrogels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 72 publications
1
26
0
Order By: Relevance
“…Color-coded chitosan hydrogels are used for rapid, sensitive, and specific detection of bacterial enzymes [142] Preparation and characterization of hydrogels obtained from chitosan and carboxymethyl chitosan Preparation and characterization of hydrogels [156] Chitosan and cellulose-based hydrogels for wound management Wound dressing materials [157] Agarose Nanosilicate embedded agarose hydrogels with improved bioactivity Nanocomposite agarose hydrogel to promote cell binding, growth, and proliferation [108] Facile formation of agarose hydrogel and electromechanical responses as electro-responsive hydrogel materials in actuator applications…”
Section: Polymerization Monomers Of the Synthetic Polymer Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Color-coded chitosan hydrogels are used for rapid, sensitive, and specific detection of bacterial enzymes [142] Preparation and characterization of hydrogels obtained from chitosan and carboxymethyl chitosan Preparation and characterization of hydrogels [156] Chitosan and cellulose-based hydrogels for wound management Wound dressing materials [157] Agarose Nanosilicate embedded agarose hydrogels with improved bioactivity Nanocomposite agarose hydrogel to promote cell binding, growth, and proliferation [108] Facile formation of agarose hydrogel and electromechanical responses as electro-responsive hydrogel materials in actuator applications…”
Section: Polymerization Monomers Of the Synthetic Polymer Hydrogelsmentioning
confidence: 99%
“…For example, Xiao et al reported color-coded chitosan hydrogels that can be used for rapid, specific, and sensitive detection of bacterial enzymes, as well as selective detection of bacteria through the characteristic enzyme reactions. [142] Nano-cellulose is a famous reproducible biopolymer which is released from cellulose fiber through multiple processes, such comments as acid hydrolysis, chemical fiber formation or mechanical treatment. [143] Because of its rich surface charges and surface functional groups, Nano-cellulose has potential application prospects as carriers/dispersants.…”
Section: Polymerization Monomers Of the Natural Polymer Hydrogelsmentioning
confidence: 99%
“…Chitosan is also playing a very important role in the area of sensor development, especially in the topic of biological evaluation. The versatility of chitosan in forming various forms of structures such as films, microgel/hydrogel and nanocomposites, and its adhesive properties are the main reasons for its being a popular candidate for sensor development [191,192]. These chitosan nanocomposite-based biosensors have shown high sensitivity, selectivity, and stability for detecting a variety of targets, ranging from biomolecules, DNA, and microorganisms.…”
Section: Current Research Trends On Chitosanmentioning
confidence: 99%
“…Furthermore, these membranes must be non-toxic and biocompatible to minimize the risk of epithelialization or allergic reactions. In this context, the use of enzymes [54][55][56][57], hydrogels [6,41,[58][59][60], and conductive polymers such as polyaniline (PANI) [61][62][63][64], polypyrrole (PPy) [65][66][67], polythiophene (PT) [68][69][70], or polyethylene dioxide thiophene (PEDOT) [43,[71][72][73][74] has been reported for the development of bioelectrodes due to their biocompatibility, conductivity, and the presence of tunable functionalities. However, its application in the development of biosensors is limited by different reasons and challenges to overcome, such as its relative fragility; its decrease in properties against variations in the pH of the medium, possible degradation in toxic or reactive compounds; and in some cases the use of synthesis processes and complex manufacturing procedures that are difficult to implement outside the laboratory scale [70][71][72][73][74][75][76].…”
Section: Wearable Membranes Sensormentioning
confidence: 99%